Exploring the Evolution of a Manufacturer’s Capabilities and Managers’ Mindsets When Transitioning from Closed Innovation to Open Innovation Ecosystem - Orre, Elias (My University, 2023)
Organizations in the 21st century have started to opt for open innovation instead of closed innovation for numerous reasons. Opting for open innovation allows organizations to decide how to orchestrate it. One popular theme of open innovation is innovation ecosystems. This study scrutinizes how a manufacturer’s capabilities and managers’ mindsets evolve when transitioning from closed innovation to orchestrating an open innovation ecosystem. To be able to scrutinize how the manufacturer’s capabilities and the managers’ mindsets evolve, it is essential to employ a microfoundational approach. This study’s theoretical background is built by examining three main concepts. First, closed and open innovation are examined, and reasons for organizations employing open innovation are explicitly looked at. Secondly, the ecosystem concept, specifically the innovation ecosystem concept, is delved into. Thirdly, the dynamic capability is examined thoroughly, and microfoundational research has a role important in this part. Altogether, the three concepts are combined for a working theoretical framework. This empirical study employs a single case study. The case organization in this study is stock-listed and was selected due to the unique innovation ecosystem it orchestrates. Furthermore, the innovation ecosystem is in the evolution phase, and this is why there are visible changes in managers’ mindsets and capabilities. Primary data was gathered through semi-structured interviews, while secondary data was gathered from annual reports, capital market days, and other publicly available information. The data analysis occurs through a within-case study. This study’s findings showcase numerous mindset, cognition, work method, process, and organizational routines, which enable open innovation in an innovation ecosystem. This study’s main contribution is building an empirical framework that can be used to understand how microfoundations aid the manufacturing organization in achieving dynamic capability when the organization transitions from a closed innovation process towards an open innovation ecosystem.

2000-luvulla organisaatiot ovat alkaneet valita avoimen innovaation suljetun innovaation sijaan monista syistä. Avoimen innovaation valitseminen antaa organisaatioille mahdollisuuden päättää, miten innovointi toteutetaan ja yksi suosittu avoimen innovoinnin toteutustapa on innovaatioekosysteemi. Tässä tutkimuksessa tarkastellaan, miten teollisuusyrityksen valmiudet ja johtajien ajattelutavat kehittyvät siirryttäessä suljetusta innovaatiosta avoimen innovaatioekosysteemin organisointiin. Yrityksen kyvykkyyksien ja johtajien ajattelutapojen kehittymistä tarkastellaan mikroperusteiden näkökulmasta. Tämän tutkimuksen teoreettinen tausta rakentuu kolmen pääkäsitteen tarkastelun kautta. Ensiksi tarkastellaan suljettua ja avointa innovointia ja syitä, joiden vuoksi organisaatiot käyttävät avointa innovointia. Toiseksi syvennytään ekosysteemin käsitteeseen, erityisesti innovaatioekosysteemin käsitteeseen. Kolmanneksi tarkastellaan dynaamisia kyvykkyyksiä mikroperusteiden avulla. Nämä kolme käsitettä yhdistetään toimivaksi teoreettiseksi kehykseksi. Tämä empiirinen tutkimus on yksittäinen tapaustutkimus. Tutkimuksen tapausorganisaatio on pörssilistattu ja se valittiin sen organisoiman ainutlaatuisen innovaatioekosysteemin vuoksi. Lisäksi innovaatioekosysteemi on kehitysvaiheessa, joten johtajien ajattelutavoissa ja kyvyissä on nähtävissä muutoksia. Ensisijainen aineisto kerättiin puolistrukturoiduilla haastatteluilla. Toissijaista aineistoa kerättiin vuosikertomuksista, pääomamarkkinapäivistä ja muista julkisesti saatavilla olevista tiedotteista. Tutkimuksen tulokset osoittavat lukuisia erilaisia ajattelutapoja, kognitiota, työmenetelmiä, prosesseja ja organisaation rutiinimuutoksia, jotka mahdollistavat avoimen innovaation toteutumisen innovaatioekosysteemissä. Tämän tutkimuksen tärkein anti on empiirisen kehyksen luominen, jonka avulla voidaan ymmärtää, miten mikroperustat auttavat tämän tutkimuksen teollisuusyritystä saavuttamaan dynaamisen kyvykkyyden, kun organisaatio siirtyy suljetusta innovaatioprosessista kohti avointa innovaatioekosysteemiä.
Keywords: capability; dynamic capabilities; capability; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development